EVALUATING THE ROLE OF FINANCIAL INTERMEDIARIES IN ECONOMIC DEVELOPMENT (International Journal of Food and Nutritional Sciences, 2022)
This paper evaluates the pivotal role of financial intermediaries in the economic development of India, emphasizing their contributions to financial inclusion, small and medium-sized enterprises (SMEs), and overall economic growth. Financial intermediaries, including commercial banks, microfinance institutions (MFIs), and non-banking financial companies (NBFCs), serve as essential conduits between savers and borrowers, facilitating the efficient allocation of resources across various sectors of the economy. In a country where a significant portion of the population remains unbanked, MFIs have emerged as critical players, providing access to credit for low-income individuals and empowering them to invest in education, health, and entrepreneurship. This access has been instrumental in alleviating poverty and promoting economic self-sufficiency. Furthermore, institutions like the Small Industries Development Bank of India (SIDBI) support SMEs by offering tailored financial products and services, enabling these enterprises to thrive and contribute significantly to job creation and GDP.